SHELF LIFE TEST OF FEED ADDITIVE FROM ENCAPSULATED ACIDIFIER AND PHYTOBIOTIC MIXTURES BASED ON PACKAGING MATERIALS AND STORAGE TIME - Ruli Nanda Pratama; Osfar Sjofjan; Eko Widodo (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2014)
The aims of this study were to evaluate: 1) the effect of using different packaging materials on the shelf life of feed additive from acidifier and phytobiotic mixture in encapsulated form and 2) the effect of storage time on the shelf life of feed additive from acidifier and phytobiotic mixture in encapsulated form. The materials used were lactic acid, citric acid, garlic, Phylanthus niruri L., whey, gum arabic, BHT, and microwave oven. The method used was laboratory experiment using Nested Completely Randomized Design. Twenty five treatments were differentiated on five packaging materials, namely PP (P1), OPP (P2), PE (P3), HDPE (P4), and LLDPE (P5) plastics and nested to five storage times, namely 0 (L0), 2 (L2), 4 (L4), 6 (L6), and 8 (L8) weeks. Each plastic had a size of 10 x 8 x 0.03 cm (length, width, and thickness). Storage had been done at room temperature, while daily temperature and humidity were recorded. The variables observed were water content, aw, and molds and yeast TPC. Data were analyzed using analysis of variance followed by Duncan's Multiple Range Test. The results showed that the packaging materials and storage time gave a significant effect (P<0.01) on water content, aw and molds and yeast TPC of feed additive in encapsulated form. The results of Duncan's Multiple Range Test showed that feed additive in encapsulated form that packed in OPP plastic for 0 week as the best treatment on water content, aw, and molds and yeast TPC. The conclusion of this study were: 1) OPP plastic gave the best results on the shelf life of feed additive in encapsulated form and 2) the increasing of storage time could decline the quality of feed additive in encapsulated form. It is suggested to use OPP plastic for packaging with a thickness of more than 0.03 cm and in vacuum packaging techniques. Keywords: shelf life, feed additive, encapsulated, acidifier and phytobiotic mixtures, packaging materials, storage time